PENERAPAN ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI LEMBAGA PERMASYARAKATAN - Aris, Mohamad Syaiful; Tambunan, Ezra; Putri, Dita Elvia Kusuma; Nugraha, Xavier (LITIGASI, 2022)
Public service is a series of actions carried out in order to meet the service needs of each citizen. In the department of corrections, public service arrangements also hold an essential element in creating a quality environment. It is on the reason that prisoners as god's creatures are also entitled to proper service as is guaranteed by article 34 verses (3) of Constitution 1945. On the other hand, in implementing abovementioned, service in correctional service is not actually implemented properly. This is due to many factors, such as shortage of prison officers, overcrowded prison, and other factors.  Based on abovementioned, the author formulated 2 (two) legal problems: a) the prisoner's right to good public service under the Correctional Service Act; and b) AUPB applications upon service arrangements in the penitentiary. The method of research is legal research. It is concluded that: a) eventhough a convict has committed an offense, the state has to ensure he gets proper service during his time; b) Public service officers in prison should always refer its conduct to the General Principles of Good Governance such as impartiality, good service, and principle to not commit abuse of power. Keywords: Penitentiary, Public Services, AUPB.